Positive end-expiratory pressure at minimal respiratory elastance represents the best compromise between mechanical stress and lung aeration in oleic acid induced lung injury - Carvalho, Alysson Roncally S. (2007)
João HN Soares helped during the anaesthetic procedure. This work was partly supported by the Brazilian Agencies CNPq, CAPES and FAPERJ.